Risk of benign tumours of nervous system, and of malignant neoplasms, in people with neurofibromatosis: population-based record-linkage study. - Seminog, O; Goldacre, M (2013)
BACKGROUND: The neurofibromatoses (NF) are genetic disorders. Increased risks of some cancers in people with NF are well recognised, but there is no comprehensive enumeration of the risks across the whole range of site-specific cancers. Our aim was to provide this. METHODS: A linked data set of hospital admissions and deaths in England was used to compare rates of tumours in an NF cohort with rates in a comparison cohort, with results expressed as rate ratios (RR). RESULTS: The RR for all cancers combined, in people with both types of NF combined, was 4.3 (95% confidence interval (CI): 4.0-4.6), based on 769 cases of cancer in 8003 people with NF. Considering only people with presumed NF1 (as defined in the main article), the RR for all cancers excluding nervous system malignancies remained elevated (2.7, 95% CI: 2.4-2.9); and risks were significantly high for cancer of the oesophagus (3.3), stomach (2.8), colon (2.0), liver (3.8), lung (3.0), bone (19.6), thyroid (4.9), malignant melanoma (3.6), non-Hodgkin's lymphoma (3.3), chronic myeloid leukaemia (6.7), female breast (2.3) and ovary (3.7). CONCLUSION: Neurofibromatosis was associated with an increased risk of many individual cancers. The relationships between NF and cancers may hold clues to mechanisms of carcinogenesis more generally.